IMPLEMENTASI KEBIJAKAN DISIPLIN ASN PADA BAGIAN KEUANGAN SEKRETARIAT DAERAH KABUPATEN JAYAPURA - Jamaludin, Jusmiyati; Muhdiarta, Untung; Aedah, Nur (Universitas Cenderawasih, 2024)
This research aims to analyze the implementation of disciplinary policies for the State Civil Service in the Finance Section of the Regional Secretariat of Jayapura Regency; and analyze and describe factors that support and hinder the implementation of disciplinary policies for the State Civil Apparatus in the Finance Section of the Regional Secretariat of Jayapura Regency. The research approach used in this research is a descriptive research approach with a qualitative approach. The results of the research show that the implementation of the State Civil Apparatus discipline policy in the Finance Section of the Regional Secretariat of Jayapura Regency according to the theory of Donald Van Meter and Carl Van Horn, based on the size and objectives of the policy, has become the basis for the State Civil Apparatus to work according to the Main Duties and Functions of each position. owned by employees; Human resources are quite good; The characteristics of the implementing agent are in accordance with applicable regulatory provisions; The attitudes and tendencies (Disposition) of implementers are still not understood in depth; Communication between organizations has been carried out in accordance with existing disciplinary regulations, namely coordination with the Regional Personnel Agency (BKD) of Jayapura Regency; and The external environment which includes the economic, social and political environment of ASN and the environment influences employee discipline. Supporting factors include enforcement of disciplinary rules; ease of policy content and employee environmental conditions, while inhibiting factors consist of employees lacking time discipline and less effective use of facilities.